Progress of researches on the internalization of Escherichia coli O157:H7 in plant tissues - Yang Li; Wang Haizhen; Yao Zhiyuan; Wu Jianjun (浙江大学学报. 农业与生命科学版)
Shiga toxin-producing Escherichia coli O157:H7, one of the most emergent foodborne pathogens, can cause illnesses ranging from diarrhea to hemorrhagic colitis and hemolytic-uremic syndrome. Escherichia coli O157: H7 is spread into the environment via fecal shedding or field application of farm effluent. The produce can be contaminated by E. coli O157:H7 through soil, feces, irrigation water, manure application, insects, or postharvest washing. Fresh produces, especially leafy greens that be consumed raw, are increasingly being recognized as the foremost transmitting vehicles. Many studies have shown that E. coli O157:H7 can internalize within a variety of tissue types. Although the internalized E. coli O157:H7 makes no difference to the normal growth of plants, it brings risks when people take in the unpasteurized fresh food. In this review, sources of contamination, main routes of internalization, interactions between internalized E. coli O157:H7 and the plant host as well as other microbes were stated.The internalization of E. coli O157:H7 in fresh produce has been found to be associated with many routes including stomata, lenticels, sites of root emergence and sites of biological or physical damage. Because stomata are generally found in greater densities on the underside of leaves, greater internalization of E. coli O157:H7 on leaves would be likely on the abaxial side than on the adaxial side. Root uptake of E. coli O157:H7 and subsequent internalization has also been widely reported. Damaged leaves release more nutrients onto the leaf surface, which allow E. coli O157:H7 to grow and induce more E. coli O157:H7 to get into the leaves. Various factors including growth substrate, inoculums level, and plant species and cultivar, have shown to affect the level of internalization.Although there is no obvious change on the appearance of the plant, complicated interactions between internalized E. coli O157:H7 and the plant hosts have been discovered. Plant hosts have some pattern recognition receptors (PRRs) to recognize pathogen associated molecular patterns (PAMPs), and further activate plant immune response to limit the growth and spread of the pathogen. PAMPs contain flagellin, peptidoglycan, lipopolysaccharide, and other components which derived from pathogens. Studies have showed that elimination of these PAMPs leads to better growth of E. coli O157:H7 in the plant. Furthermore, phytopathogen can grow in the plant through secreting effector proteins to disturb the recognition of PAMPs by PRRs. Whether human pathogen currently carries the effector proteins is yet to be determined. Further research is needed to explain the mechanism of E. coli O157:H7 invasion and growth in the plant hosts. In addition, interactions between E. coli O157:H7 and the epiphytic microbes would affect the internalization of E. coli O157:H7. The metabolic products of the epiphytic microbes and the competition of nutrients between E. coli O157:H7 and the epiphytic microbes could limit the growth of E. coli O157:H7. On the other hand, some epiphytic microbes could produce available carbon sources to help E. coli O157:H7 grow and get into the plant hosts.In short, better understanding of the internalization of E. coli O157:H7 in plants and risks will be helpful in reducing the pathogenic infection to human. Further researches remain to be done in revealing the molecular and genetic details of the mechanisms that are involved to control the contamination of fresh produce by human pathogenic bacteria.